O uso de aplicativos como instrumento de estímulo pedagógico direcionado ao ensino e aprendizagem de geometria plana no 9º ano do ensino fundamental - MEDEIROS, Israel Alves de Ananias (2022)
ABSTRACT This research is on the use of digital applications in the teaching-learning process of Plane Geometry in a public school located in the municipality of São João do Sóter - MA. It aims to verify whether digital applications can serve as an instrument to encourage students, as well as facilitate the subject. In this perspective, it is proposed the production of the Geotheke digital technological application, as well as its manual, aiming to equip students and teachers to use this tool in Plane Geometry classes, making them more attractive so that students can participate more. It is a qualitative research, having as methodology the instrumental case study of exploratory nature. The research subjects are students at the 9th grade of elementary school and their teacher. The research data were obtained through the following instruments: a) questionnaire applied to students both online and in person, in the hybrid model; b) interview with the teacher; and c) systematic observations in activities involving questions about plane geometry, applied to students. For analysis of the results, Duval (1993, 1995, 2003, 2007, 2013) and Neres (2010, 2015, 2016) were used as references, with the support of the Theory of Semiotic Representation Registers (TRRS). The survey results indicated that students have difficulties in solving geometry problems. However, they demonstrated yields of approximately 60% from the technology used. In relation to the teacher, it was observed that he is in the process of training as an e-mature professional, as he has already progressively started his ability to recognize and use digital technological resources in his personal and professional environment, developing digital maturity, becoming a professional with “digital influence”, which results in didactic and methodological improvements. In practice, it is about the teacher making use of digital technologies in their practice as an instrument to carry out the social transformation of their students. It is concluded that teaching with the use of digital applications produces stimulation, participation and learning facilitation, making classes more attractive.